2022
DOI: 10.1080/26410397.2022.2136027
|View full text |Cite
|
Sign up to set email alerts
|

Ageing in obscurity: a critical literature review regarding older intersex people

Abstract: Intersex people experience a range of human rights abuses, including non-consensual, irreversible medical interventions on minors. These abuses have lifelong effects, yet little is known about older intersex people. People in this diverse group face multiple marginalisations and erasures across different policy and practice arenas. This article reviews literature about intersex issues, drawing out materials relevant to older intersex people using an historically grounded approach. It focuses on the key issues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…The latter is largely missing in the transition to adult care, as almost all the participants mentioned it in the focus groups, even though the research on transition of care emphasizes the importance of psychosocial services in the transition of care [20]. This finding is all the more striking and makes the push for psychosocial support in the adult care vital, since the literature on quality of life in adult people with VSCs reveals that they experience a range of serious health issues, such as depression, anxiety, and suicidality [24,44,45], in comparison to the general population; feel stigma around their bodies and sexualities [46][47][48]; and age in poor psychosocial conditions [24]. Even though the rights of children did not feature prominently in the discussion, they were in the background as a position, because the participants highlighted the importance of child-oriented care and the time and resources dedicated to pediatric care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter is largely missing in the transition to adult care, as almost all the participants mentioned it in the focus groups, even though the research on transition of care emphasizes the importance of psychosocial services in the transition of care [20]. This finding is all the more striking and makes the push for psychosocial support in the adult care vital, since the literature on quality of life in adult people with VSCs reveals that they experience a range of serious health issues, such as depression, anxiety, and suicidality [24,44,45], in comparison to the general population; feel stigma around their bodies and sexualities [46][47][48]; and age in poor psychosocial conditions [24]. Even though the rights of children did not feature prominently in the discussion, they were in the background as a position, because the participants highlighted the importance of child-oriented care and the time and resources dedicated to pediatric care.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is increasing awareness among professionals regarding the requirements for transitioning care, the evidence indicates that there is still significant opportunity for enhancement [20]. Adults with VSCs experience health problems that have been either created or worsened by medical interventions [24]. The research has identified several obstacles to the successful transition of care, for example, insufficient training in adolescent health care, potential diffusion of responsibility among pediatric and adult care providers, the complexity of health care conditions, inadequate communication between pediatric and adult health care providers, the need for meaningful inclusion of adolescents and young adults in the transition process, lack of planning and coordination of services, and insufficient evidence to guide the development of transition of care [20,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reviewed authors question the human rights violations that intersex people face, denouncing the practice of non-consensual surgeries on the sex characteristics of intersex newborns, children, and adolescents (Ammaturo 2016b;Bastien-Charlebois and Guillot 2018;Bauer et al 2020;Carpenter 2016Carpenter , 2018aCarpenter , 2018bCarpenter , 2020Crocetti et al 2020a;Davidian [2011Davidian [ ] 2013Ghattas 2013;Guillot 2018;Mestre Martínez 2022;Monro et al 2019;Paechter 2021;Winter Pereira 2022;Zelayandía-González 2023). Furthermore, they identify a lack of adequate health care throughout their lifespan (Berry and Monro 2022;Crocetti et al 2020b;Crocetti et al [2023] 2024), as well as dynamics of social discrimination and exclusion in different contexts (Carpenter 2020;Sterling 2021;Winter Pereira 2022).…”
Section: Human Rights Frameworkmentioning
confidence: 99%
“…There are also few studies internationally on older people with intersex conditions, which may have to do with the fact that intersex conditions are often brought to light at birth or in adolescence, and that research on experiences of living with intersex conditions is generally inadequate. This is despite the fact that these people often have experiences of surgical interventions and hormone therapy without consent, which then has consequences for the rest of their lives, but is rarely followed up (Berry & Monro, 2022). As Latham & Barrett (2015) point out, older people with intersex variations may have been on hormone therapy for many years, have traumatic experiences from the healthcare system, and have concerns about future care needs, especially for intimate care when the body is exposed (Latham & Barrett, 2015).…”
Section: Description Of the State Of The Researchmentioning
confidence: 99%